Poorer performance on physical frailty-related parameters is associated with depression among older rural Indians - Jonas S. Sundarakumar; Pravin Sahadevan; Aishwarya Hiremath; Sakshi Arora; Pooja Rai (Scientific Reports, 2025)
Abstract The role of physical factors in depression is prominent but often underrecognized in the aging population. The potential relationship between physical frailty and depression among older adults has been understudied in the rural southern Indian population. We aimed to examine if there is a cross-sectional association between three objective physical frailty-related parameters (handgrip strength, HGS; timed up-and-go, TUG test; chair stand Test, CST) with depression (assessed using the Geriatric Depression Scale, GDS-30) among 4455 participants aged ≥ 55 years from a rural population in Karnataka, India. Binary logistic regression was used to test the association between each of the three frailty-related parameters and depression. Odds ratios (OR) along with 95% confidence intervals (Cl) were estimated, adjusting for covariates (age, sex, education, marital status, income, current tobacco use, current alcohol use, body mass index, number of medical comorbidities, and family history of depression). We found that for every kilogram increase in HGS and every point increase in the CST score, there was 0.97 (95% CI 0.96–0.99, p = 0.008) and 0.93 (95% CI 0.90–0.96, p < 0.001) times lower odds of depression, respectively, whereas each unit of increase in TUG time was associated with 1.05 (95% CI 1.03–1.08, p < 0.001) times higher odds of depression. We underscore the clinical importance of routine physical frailty assessments in older adults, as specific frailty-related parameters could potentially predict depression.